An Abnormal Signal Diagnostic Emendation Technique Research - Tiejun Cao (Institute of Advanced Engineering and Science, 2015)
This paper introduced a sort of abnormity data method. We start with analysing an example first and carry through theory deducing once more and list this method arithmetic step and application field finally. With the development information and control technology, we need more and more important and imminent to diagnose abnormity data and eliminate them. The quality of measuring data is improved availably by the application of data emendation technique. DOI: http://dx.doi.org/10.11591/telkomnika.v13i1.6695